Combined effect of waste colemanite and silica fume on properties of cement mortar - Erdoğmuş, Ertuğrul; Erdoğmuş, Ertuğrul (Walter De Gruyter Gmbh, 2014)
In this study, effect of silica fume (SF) waste colemanite on properties of cement mortar was investigated. The parameters studied were initial and final setting times, specific gravity, specific surface, water demand, flow ability, volume expansion, compressive strength, and freeze-thaw durability. A number of mixtures were prepared by the replacement of Portland cement with SF and waste colemanite. The results showed that the initial and final setting times of cement pastes were generally retarded when the SF and waste colemanite replaced part of the cement. It was observed that the inclusion of SF increases compressive strength of the specimens in 28 days compared with that of the control concrete. However, those of the specimens with colemanite decrease both early and later days. Up to 10% and 12% colemanite content in the mixture, strength loss of specimens after freeze-thaw cycles is below the limit permitted.
Keywords: Cement; Colemanite; Silica Fume